Intermediação de mão de obra: análise do perfil e da experiência dos trabalhadores no Sistema Nacional de Emprego (SINE) - Santos, Yara Nunes dos (2023)
This research aims to investigate the experiences of individuals seeking job opportunities through the National Employment System (SINE). To achieve this objective, a combination of qualitative and quantitative methodologies was employed, utilizing data extracted from government systems to comprehend prevalent job vacancies and the characteristics of individuals utilizing the public labor intermediation service. Additionally, interviews were conducted with individuals present at SINE locations to gain insight into their personal experiences during the job search process. The study evaluates the effectiveness of SINE in worker (re)placement within the labor market, considering the societal reorganization and economic phenomena influencing employment patterns and living conditions of the population. Data analysis revealed the most frequent job vacancies, offering valuable insights into the local labor market and areas of high demand. Moreover, the interviews provided a qualitative perspective on the experiences, challenges, and expectations of individuals concerning the SINE service. The results obtained from this research contribute to a deeper understanding of the requirements and preferences of those utilizing public labor intermediation services in their employment search.